Claus Bjørn, Grundtvig som politiker - Udgivet af Thorkild C. - Wåhlin, Vagn; Pedersen, Kim Arne (Grundtvig-Studier, 2009)
Claus Bjørn, Grundtvig as politician - published by Thorkild C. Lyby Reviewed by Vagn Wåhlin and Kim Arne Pedersen